2011
DOI: 10.1109/tgrs.2011.2162960
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Polarized TerraSAR-X Data for Oil-Spill Observation

Abstract: The Synthetic Aperture Radar (SAR) is unanimously recognized as the most important remote sensing tool for sea oil spill monitoring. The TerraSAR-X satellite can provide highquality, multi-mode X-band SAR-data from Ocean surface for scientific research and associated applications. For the purposes of this study Single Look Slant Range Complex (SSC) Dual Polarization StripMap (SM) TerraSAR-X products are employed. Physically based polarimetric approaches, aimed at exploiting fully the information carried on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 21 publications
2
86
0
Order By: Relevance
“…In this regard, the Deepwater Horizon oil spill has serious effects on feeble maritime, wildlife habitats, Gulf's fishing, coastal ecologies and tourism industries. As a result, human health problems are caused because of the spill and its clean-up [25]. Consistent with Marghany and Hashim [7], Synthetic aperture radar (SAR) is a precious foundation of oil spill detection, surveying and monitoring that improves oil spill detection by various approaches.…”
Section: Introductionmentioning
confidence: 87%
“…In this regard, the Deepwater Horizon oil spill has serious effects on feeble maritime, wildlife habitats, Gulf's fishing, coastal ecologies and tourism industries. As a result, human health problems are caused because of the spill and its clean-up [25]. Consistent with Marghany and Hashim [7], Synthetic aperture radar (SAR) is a precious foundation of oil spill detection, surveying and monitoring that improves oil spill detection by various approaches.…”
Section: Introductionmentioning
confidence: 87%
“…This feature will be a function of the root mean square (RMS) slope (large-scale roughness), dielectric constant, and the incidence angle [2] (as shown in Table IV). Studies related to this feature have found low values (low HH-VV correlation) for oil covered areas, and high values for open water regions using both C-and X-band SAR [2] [44].…”
Section: Factorsmentioning
confidence: 99%
“…With the advent of polarimetric SARs, new, effective, and automatic physical approaches have been conceived to locate and monitor oil spills [Gade et al, 1998;Migliaccio et al, 2011Migliaccio et al, , 2009aMigliaccio et al, , 2009bNunziata et al, 2011Nunziata et al, , 2010Nunziata et al, , 2008Velotto et al, 2011;Zhang et al, 2011]. These new approaches exploit the correlation characteristic between and among polarimetric signals when crude oil at sea is observed.…”
Section: Polarimetric Sar Observationmentioning
confidence: 99%
“…This is not the case for an oil-covered sea surface due to oil's heavy damping properties. This behavior has been successfully exploited in the development of simple and effective filtering techniques to observe oil at sea in dual-polarimetric SAR data [Migliaccio et al, , 2009a[Migliaccio et al, , 2009bVelotto et al, 2011]. When a fully polarimetric SAR is available, the hv or vh polarimetric signals can be used along with the hh and vv channels to develop techniques that are able to provide a simple and logical true or false output that limits uncertainties in interpretation [Migliaccio et al, , 2009bNunziata et al, 2011Nunziata et al, , 2008Zhang et al, 2011].…”
Section: Polarimetric Sar Observationmentioning
confidence: 99%